2023
DOI: 10.1093/femsre/fuad010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial virulence regulation through soluble peptidoglycan fragments sensing and response: knowledge gaps and therapeutic potential

Abstract: Given the growing clinical-epidemiological threat posed by the phenomenon of antibiotic resistance, new therapeutic options are urgently needed, especially against top nosocomial pathogens such as those within the ESKAPE group. In this scenario, research is pushed to explore therapeutic alternatives and, among these, those oriented towards reducing bacterial pathogenic power could pose encouraging options. However, the first step in developing these anti-virulence weapons is to find weak points in the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 175 publications
4
14
1
Order By: Relevance
“…Therefore, based on previous publications ( 56 60 ) and our results, we believe that the mildly reduced virulence of Kp52.145RΔAG TC (DHA-1) and Kp52.145RΔAG pUCP-DHA-1 transformant could lean on a greater parallel peptidoglycanase activity of DHA-1 compared to that of CMY-2, which seems devoid of significant associated burdens even when overproduced ( Fig. 1 and 2 ).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Therefore, based on previous publications ( 56 60 ) and our results, we believe that the mildly reduced virulence of Kp52.145RΔAG TC (DHA-1) and Kp52.145RΔAG pUCP-DHA-1 transformant could lean on a greater parallel peptidoglycanase activity of DHA-1 compared to that of CMY-2, which seems devoid of significant associated burdens even when overproduced ( Fig. 1 and 2 ).…”
Section: Resultssupporting
confidence: 75%
“…In this regard, some studies have shown that the production of certain β-lactamases (e.g., some OXA-2-derived extended spectrum variants) entails dramatic biological costs and virulence attenuations in P. aeruginosa, while similar outputs have been obtained for other gram-negatives. These effects have been proposed to be likely mediated by residual activities of β-lactamases on peptidoglycan and/or muropeptide-based regulatory networks ( 40 , 56 60 ). In this study, we wanted to decipher whether or not the production of acquired AmpCs could impair K. pneumoniae pathogenic power in a similar way.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…aeruginosa infection, including biofilm formation cell-secreted factors, as well as several anatomical structures, including pili, flagella, and LPS . These factors all serve as potential drug targets for improved treatment modalities where new antibiotics are desperately needed to combat these bacteria in the clinic. It is well known that these bacteria, like others, are able to shed and remodel their PG structures; however, few studies have been able to distinguish PG as a definitive virulence factor during infection. Additionally, current investigations examining the dynamic changes in PG topology and architecture during infection involve the use of denaturing methods to isolate PG for downstream assaying. Here, we sought to utilize our fast and robust minimal tetrazine probe to execute dynamic in situ labeling of the PG anatomy in live bacteria to serve as a platform for many potential downstream applications. Previous attempts to label these species resulted in either low incorporation, high background, or unusual morphology and nonspecific labeling when labeled with SPAAC. , Use of the new HTz-NAM and aTCO-SiR labeling strategy resulted in markedly improved labeling and notably less background in the NAM-treated sample in P. putida (Figure A, SI Figures 33 and 34).…”
Section: Resultsmentioning
confidence: 99%